Características morfométricas de abelhas africanizadas: uma abordagem quantitativa e molecular - Rodrigues, Marisa C. [UNESP] (2020)
In Apis mellifera L. bees, the reproductive performance of queens is characterized by a set of traits with increasing relevance in international beekeeping due to its high associated economic value. Genetic parameters for reproduction-associated traits are very important, since present, in the Africanized honeybees, interesting genetic correlations with some morphometric traits, such as emergence weight with the weight of the ovaries. However, there are not many studies that include estimation of genetic parameters with genomic approaches so that the physiological aspects are understood at the level of quantitative and molecular genetics, simultaneously. In this present study, I proposed to estimate genetic parameters for the queen's weight at emergence and also identify polymorphisms in the gene previously indicated as a candidate: vitellogenin gene (Vg), for weight at emergence. In this way, we aim to contribute to a better understanding of the gene approaching physiological processes that influence their reproductive performance, in order to improve national beekeeping and leverage and inspire new research focused to unravel the reproductive biology of bees.